Benefits of psychosocial intervention and continuity of care by child and family health nurses in the pre‐ and postnatal period: process evaluation. (30th November 2012) - Kemp, Lynn; Harris, Elizabeth; McMahon, Catherine; Matthey, Stephen; Vimpani, Graham; Anderson, Teresa; Schmied, Virginia; Aslam, Henna
Abstract: Aim: To report a programme theory for pre‐natal home visiting by nurses in the context of a sustained nurse home visiting programme by exploring pre‐ and postnatal outcomes and characteristics of the intervention that may have contributed to the outcomes. Background: Studies have shown sustained nurse home visiting commencing pre‐natally to be effective. Few studies have explored the processes by which pre‐natal activities by nurses contribute to achieving effective outcomes. Design: Process evaluation. Methods: Process and outcome data from a randomized controlled trial of sustained nurse home visiting in an area of socioeconomic disadvantage in Western Sydney between 2005–2008 were collated. The pre‐natal intervention focused on improving transition to parenting by supporting mothers through pregnancy. Health and service use outcome data were analysed for 208 women (111 intervention; 97 comparison receiving usual care). Five nurses delivering the intervention completed checklists detailing activities undertaken. Results: Nurses provided information, psychosocial support, and health promoting activities for families. Intervention mothers had a higher rate of unassisted vaginal births than the general population. Compared with comparison mothers, intervention mothers at 4–6 weeks postnatally reported better general health and felt significantly more enabled to cope with and understand their baby and to care for themselves and their baby. Conclusion: Comprehensive support, in a context of enabling client‐nurse relationships and continuity of carer are the ways by which antenatal nurse home visiting achieves benefits for women and infants, having an impact on both clinical outcomes such as rates of normal vaginal delivery and maternal service engagement.